2016
DOI: 10.1007/s00586-016-4451-2
|View full text |Cite
|
Sign up to set email alerts
|

Anterior versus posterior approach in surgical treatment of tuberculous spondylodiscitis of thoracic and lumbar spine

Abstract: Both anterolateral and posterolateral approaches are sufficient for achieving the goals of surgical treatment of thoracic and lumbar Pott's disease but posterolateral approach allows significant better kyphotic angle correction, less angle loss, better improvement in back pain but unfortunately more operative time and blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 29 publications
3
50
0
Order By: Relevance
“…It allows direct access to the pathology, adequate debridement, adequate decompression, and the ability to place a large graft. But it is more challenging in patients with lumbarsacral spinal infections due to the complicated regional anatomy, and may increase the risk of surgery-related morbidity [17]. Also, anterior instrumentation at L4-L5 and L5-S1 is potentially dangerous and insubstantial [18].…”
Section: Discussionmentioning
confidence: 99%
“…It allows direct access to the pathology, adequate debridement, adequate decompression, and the ability to place a large graft. But it is more challenging in patients with lumbarsacral spinal infections due to the complicated regional anatomy, and may increase the risk of surgery-related morbidity [17]. Also, anterior instrumentation at L4-L5 and L5-S1 is potentially dangerous and insubstantial [18].…”
Section: Discussionmentioning
confidence: 99%
“…19 We retrospectively analysed the data of 43 patients who underwent single-stage posterior debridement with bone graft fusion and internal fixation and found that single posterior surgery had a shorter surgical duration and lower intraoperative bleeding volume than single anterior surgery (P < 0.05); these data are in line with a report by Zhou et al 20 We believe that this finding may be related to the greater experience in performing pedicle screw implantation and short-segment fixation of posterior pedicle screws in patients with a lower rate of loss of the kyphosis correction angle by posterior than anterior surgery (P < 0.05), which is consistent with previous reports. 21,22 In this retrospective analysis, the anterior surgical approach for thoracic TB allowed us to directly reach and thoroughly remove the lesion, enabled bone grafting and internal fixation within a larger field of vision, and achieved the goal of reconstructing the mechanical structure of the spine. Anterior surgery is more anatomically complex than posterior surgery, and several important vessels, nerves, and organs are present in front of the spine.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al [6] performed X-ray measurements of the anterior, middle, and posterior heights of thoracic and lumbar vertebrae in 124 normal subjects to calculate normal reference values for Chinese patients in clinical studies. However, the magnification differences between X-ray measurements and in vivo values will lead to errors in measurement results.…”
Section: Discussionmentioning
confidence: 99%